2019
DOI: 10.3390/ma12081206
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Layer-By-Layer Highly Stable Multilayer Films: Study of the Loading and Release of FITC-Labeled Short Peptide in the Drug Delivery Field

Abstract: A viable short FITC-peptide immobilization is the most essential step in the fabrication of multilayer films based on FITC-peptide. These functional multilayer films have potential applications in drug delivery, medical therapy, and so forth. These FITC-peptides films needed to be handled with a lot of care and precision due to their sensitive nature. In this study, a general immobilization method is reported for the purpose of stabilizing various kinds of peptides at the interfacial regions. Utilizing Mesopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Researchers have employed LBL self-assembly for the fabrication of mesoporous silica nanoparticles and HYH–cyclodextrin films, which were constructed to load the fluorescent dyes and peptides. The release rates of these molecules were varied by the variation in the number of layers in the multilayer films [ 117 , 118 ].…”
Section: Hyh–bioceramic and Hyh–bioglass Compositesmentioning
confidence: 99%
“…Researchers have employed LBL self-assembly for the fabrication of mesoporous silica nanoparticles and HYH–cyclodextrin films, which were constructed to load the fluorescent dyes and peptides. The release rates of these molecules were varied by the variation in the number of layers in the multilayer films [ 117 , 118 ].…”
Section: Hyh–bioceramic and Hyh–bioglass Compositesmentioning
confidence: 99%
“…A layer-by-layer (LBL) self-assembly has been widely utilized for surface modification and constructing stable multilayer films due to its simplicity, efficiency, repeatability, robustness, and flexibility. Moreover, the thickness of multilayer films can be well-controlled down to the nanometer level. Therefore, LBL self-assembly is considered to be an environmentally friendly manufacturing process and applied to endow large amounts of biological molecules in the membrane. Almost any type of substrate surface can be modified by LBL, including the surfaces of CLs .…”
Section: Introductionmentioning
confidence: 99%
“…The papers [ 5 , 6 ] present data about multilayer films and electrospun matrices as advanced materials used in drug delivery systems. Nie et al [ 5 ] reported on the versatile layer by layer highly stable multilayer films prepared from polymer (hyaluronic acid) and inorganic–mesoporous silica nanoparticles for the delivery of FITC-labeled short peptides. The described method improves the stability of the multilayer structure by forming covalently cross-linked super strata on the outlying areas of the films.…”
mentioning
confidence: 99%